Mechanical and thermophysical model of date palm fiber and beet pulp composite as natural thermal insulant. (25th October 2021) - Farrokh, Seyedeh Asal; Honarvar, Masoud; Ahmadi Chenarbon, Hossein
Abstract: For the transport of frozen products, it is necessary to preserve their quality and enhance their longevity. It aimed to assess the insulation performance of the composite containing date palm fiber and beet pulp in maintaining low temperature during the transport of frozen products. Therefore, this study investigated the physical, thermal, and mechanical properties of date palm fiber and beet pulp composites for different mass fractions of 0, 2.5, 7.5, and 10%, both as stand‐alone and as compounds added to hemihydrate gypsum by using the response surface method to state an optimized system. Results showed that by increasing the fractions of date palm fiber and beet pulp, the density of composite samples reduced from 880.02 kg/m 3 to 785 kg/m 3 ; however, water absorption increased significantly (by 101.39%). The highest flexural and compressive strengths of the control were, respectively, 4.6 and 26.67 MPa, whereas the lowest of said strengths were, respectively, 3.5 and 42.91 MPa in samples containing 10% palm fiber and 10% beet pulp. Additionally, for the same fiber ratios, the thermal conductivity of composite samples was reduced by 67% compared to the control sample. After optimization, the best mass ratios for palm fiber and sugar beet bagasse were, respectively, 3.05% and 10%. For these samples, water absorption was 96.69%; flexural and compressive strengths were, respectively, 6.27 and 3.87 MPa; thermal conductivity was 0.51 W/mK; and density was 844.15 kg/m 3 . These properties show that a composite insulant containing date palm fiber and beet pulp are a good candidate for developing thermal insulants. Practical applications: Reducing microbic growth and delaying fat and protein oxidation during the storage can increase the durability of food and agriculture products, particularly different types of meats and dairies. To this end, a safe cold cycle is necessary for proper preservation during transport and storage. Cold transport is the main part of the cold chain required for preserving the quality of freshly frozen degradable products. Therefore, in addition to cold storages and refrigerated transport vehicles, the packages are also important. The goal of this research is the progressing of a natural biocomposite that is used as thermal insulant. Abstract :